An Early Ḥarklean Version in a Syriac Gospel Fragmentary Manuscript (MS Or. 403) - Popa, Cătălin-Ştefan ca. 20./21. Jh. (Journal of Biblical literature, 2024)
In this article, I examine a fragmentary Syriac manuscript (MS Or. 403) identified in the Oriental Manuscripts collection of the Library of the Romanian Academy in Bucharest. Analysis of the folios indicates that the manuscript is part of the oldest known Ḥarklean version of the gospels, dating to the late seventh century. Additionally, I address several complex issues. First, the study reveals that a manuscript previously believed by scholars to have been lost—referred to as Museum Collection 3683 (formerly Archaeological Society MS 1)—still exists. Second, it demonstrates that MS Or. 403 and MS Museum Collection 3683 are fragments of the same original manuscript, the oldest extant Ḥarklean version of the gospels, which was subsequently utilized as part of a lectionary. I include here an edition and study of this fragmentary manuscript, alongside a comprehensive history of its transmission.